Actinic keratoses: Current guideline and practical recommendations Aktinische Keratosen: Aktuelle Leitlinie und praxisbezogene Empfehlungen - Nashan, D.; Hüning, S.; Heppt, Markus; Brehmer, A.; Berking, Carola (Hautarzt, 2020)
The S3 guideline “Actinic keratosis and squamous cell carcinoma of the skin” was published on 30 June 2019. Subsequently, publications, reviews and meta-analyses appeared with new questions regarding the comparability of study data and heterogeneity of the evaluations, which are caused, among other things, by divergent measurement parameters as well as insufficient consideration of pretreatments and combined treatments. This concise overview was written in the context of criticism and in view of necessary developments and research. Topics include epidemiology, pathogenesis, prevention, clinical presentation, therapy and BK5103. Therapy is divided into local destructive procedures and topical applications. Recommendations with quotation marks are based on the actual guideline. Corresponding evidence levels are given. For the implementation in daily routine basic data, side effects and features of therapeutic options are mentioned. The current developments and questions concerning actinic keratoses become clear.
CRIS-Team Scopus Importer:2020-06-09
Keywords: BK5103; Diagnosis; Precision medicine; S3 guideline; Therapy